Inovação na mídia tradicional esportiva televisiva: o caso ESPN do Brasil - Netto, Renata Soares (2020)
How does a traditional media like ESPN Brazil innovate in content production, organizational processes and business models to remain relevant to the sports fan in a constantly changing ecosystem brought about by digital evolution? And how do these areas intertwine? This literature review on innovation investigates this problem with the application of the case study methodology based on semi-structured interviews and content analysis. Its objective is to discuss the journalism crisis within the context of sports journalism and to analyze the complex context in which the object studied is situated: the sports media market, which for decades was sustained by the pay TV market but now confronts the emerging market of streaming services. At the end of the study, it is intended to present a diagnosis of ESPN Brazil that is illustrative for other market participants who also need to adapt to the new times by practicing journalism that meets each organizational mission and that be sustainable